Exploring the correlation between dental procedures and trigemino-cardiac reflex - Tsao-Li Chuang; Yu-Ting Li; Tai-Wei Feng; Hao-Hueng Chang; Chun-Pin Lin (Journal of Dental Sciences, 2025)
Background: /purpose: The trigemino-cardiac reflex (TCR) is a brainstem reflex characterized by sudden reductions in heart rate (HR) and mean arterial blood pressure (MABP) following trigeminal nerve stimulation. Although well-documented in other surgical fields, its role during dental procedures remains unclear. This study examined the association between routine dental interventions and TCR using an experimental animal model. Materials and methods: This study presented a comprehensive analysis of physiological monitoring data obtained during a series of animal experimental surgeries conducted by our research team between 2016 and 2023. Changes in HR and MABP during routine dental procedures were evaluated using two male Beagle dogs and six Lee-Sung miniature swine. Results: No significant changes in HR or MABP were observed during the scaling procedures. In contrast, root canal treatments showed the highest TCR incidence, with simultaneous HR and MABP decreases exceeding 15 % in 9.6 % of cases and 20 % in 5.6 % of cases. Tooth extraction triggered TCR in 2.7 % of 36 cases, while implant placement did not result in simultaneous HR and MABP reductions, but notable HR fluctuations were observed. Conclusion: This study indicates that discomfort experienced during dental scaling is unlikely to induce TCR, whereas root canal treatment, involving both physical and chemical stimulation, appears more likely to trigger its occurrence. Tooth extraction may similarly provoke TCR through mechanical stimulation. Although implant placement does not result in a simultaneous reduction in HR and MABP exceeding 15 % in this study, significant HR fluctuations greater than 20 % were observed, potentially representing early signs of TCR.